2011
DOI: 10.1088/0031-9155/56/22/f01
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical wave imaging for arrhythmias

Abstract: Electromechanical Wave Imaging (EWI) is a novel ultrasound-based imaging modality for the mapping of the electromechanical wave (EW), i.e., the transient deformations occurring in immediate response to the electrical activation. The correlation between the EW and the electrical activation has been established in previous studies. However, the methods used previously to map the EW required the reconstruction of images over multiple cardiac cycle, precluding the application of EWI for non-periodic arrhythmia suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 34 publications
5
95
0
Order By: Relevance
“…which means that lower frequencies and lower frame rates must be used; and the limited acoustic window in some areas, which necessitates the use of diverging beams and implies that lateral resolution decreases with depth. However, human aneurysms are also commensurately larger than the murine ones in this study, and recent work with modern imaging platforms has demonstrated that comparable beam densities, relative to the size of the aneurysm, are possible in humans (34). This work therefore suggests additional parameters to consider that may be correlated with disease outcome and that clinicians may consider on a case-by-case basis when assessing patients.…”
Section: Experimental Studies: Assessing the Stability Of Aortic Aneumentioning
confidence: 56%
“…which means that lower frequencies and lower frame rates must be used; and the limited acoustic window in some areas, which necessitates the use of diverging beams and implies that lateral resolution decreases with depth. However, human aneurysms are also commensurately larger than the murine ones in this study, and recent work with modern imaging platforms has demonstrated that comparable beam densities, relative to the size of the aneurysm, are possible in humans (34). This work therefore suggests additional parameters to consider that may be correlated with disease outcome and that clinicians may consider on a case-by-case basis when assessing patients.…”
Section: Experimental Studies: Assessing the Stability Of Aortic Aneumentioning
confidence: 56%
“…4). The travel-time (5) thus becomes: (6) Now, let (α, β, γ) be constant parameters defined by the following equations:…”
Section: 13mentioning
confidence: 99%
“…The ERM in conjunction with the transformations defined by (7) and (9) can thus be used to model tilted PWI. The difference between the travel-times given by (6) and (8) …”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to appreciate these events a temporal resolution of close to 2 ms would be necessary [1]. In the last decade propagating events have been noted in vivo using different US modalities such as Tissue Doppler Imaging (TDI) and B-mode [2][3][4][5][6][7][8][9][10]. These studies all use velocity curves to describe the electromechanical coupling.…”
Section: Introductionmentioning
confidence: 99%